T, B, and NKT Cells in Systemic Inflammation in Obstructive Sleep Apnoea - Joanna Domagała-Kulawik; Iwona Osińska; Aleksandra Piechuta; Piotr Bielicki; Tomasz Skirecki (Hindawi Limited, 2015)
Background. Obstructive sleep apnoea syndrome (OSAS) brings risk of serious complications. The study objective was to assess elements of the cellular immune response in the course of OSAS. Methods. Peripheral blood (PB) lymphocytes: T, B, NK, NKT-like, Th, Tc, and HLA DR+ T cells were evaluated by flow cytometry of 48 OSA patients; the concentration of adiponectin, interleukin 1β, and TNFα was measured by ELISA method. The OSA complication score was developed and used for statistical analysis. Results. The proportion of B cells and Th/Tc ratio were significantly lower in the BP of OSA patients when compared with control subjects (median 7.9 versus 10.9%, 0.9 versus 1.5, p<0.05). The proportion of Tc, NK, NKT-like, and HLADR positive T cells were elevated in OSA patients when compared with healthy subjects (36.4 versus 26.8, 15.5 versus 8.5, 5.7 versus 3.0, and 8.4 versus 4.5%, p<0.05, resp.) and were more pronounced in patients with metabolic syndrome. The grade of OSA complication score correlated with systemic inflammation markers and the proportion of B cells. The value of adiponectin/BMI ratio correlated significantly with SpO2 (r=0.31, p<0.05), CRP (r=-0.35, p<0.05), TNFα concentration (r=-0.36, p<0.05), and proportion of B cells (r=0.32, p<0.05). Conclusion. Lymphocytes B, Tc, NK, NKT-like, and adiponectin are involved in systemic immune response in OSA patients possibly predisposing them to cardiovascular and metabolic complications.